2001
DOI: 10.1242/jcs.114.13.2461
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces apoptosis-like death in Leishmania donovani promastigotes

Abstract: Leishmania donovani promastigotes introduced into the bloodstream by sandfly vectors, are exposed to reactive oxygen species like H2O2 during phagocytosis by the host macrophages. H2O2 can induce promastigote death, but the mechanism of induction of this death is not known. Studies presented in this paper demonstrate that exposure to 4 mM H2O2 results in a pattern of promastigote death that shares many features with metazoan apoptosis. Motility and cell survival in these parasites show a gradual decline with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…Thus, a fluorescence shift of the parasite population was observed (Figure ). These data suggested that auranofin treatment induced a process simulating apoptosis. Although other anti-leishmanial drugs (e.g., sodium stibogluconate, miltefosine, and amphotericin B) have been reported to stimulate apoptotic-like processes, we have been unable to document this in our studies. The distinctive auranofin-induced swelling of Leishmania promastigotes and induction of caspase 3/7-like activity suggests auranofin may have marked differences in its mechanism of action than other known anti-leishmanial agents.…”
Section: Resultsmentioning
confidence: 66%
“…Thus, a fluorescence shift of the parasite population was observed (Figure ). These data suggested that auranofin treatment induced a process simulating apoptosis. Although other anti-leishmanial drugs (e.g., sodium stibogluconate, miltefosine, and amphotericin B) have been reported to stimulate apoptotic-like processes, we have been unable to document this in our studies. The distinctive auranofin-induced swelling of Leishmania promastigotes and induction of caspase 3/7-like activity suggests auranofin may have marked differences in its mechanism of action than other known anti-leishmanial agents.…”
Section: Resultsmentioning
confidence: 66%
“…The effect of metal-based compounds on the activation of caspase-like proteins as well as on the inhibition of antioxidant agents has also been studied as triggers of programmed cell death. The presence of caspase-like proteases, such as the CED-3/CPP32 group of proteases (caspase 3) and the ICE family of proteases (caspase 9), are well documented and play fundamental roles in the apoptotic cascade of Leishmania [ 51 , 52 ]. Compounds derived from silver and copper have already been reported in the activation of these proteases and their consequent action in triggering the process of cell death by apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…These events lead to parasite membrane disruption through peroxidation and the release of intracellular Ca stores, which frequently result in apoptosis. 7,[69][70][71][72][73][74] We cannot rule out the possibility that the same mechanisms are induced after the internalization and dissolution of NPCs by macrophages, given that the introduction of Sb(V) into NPCs allows the delivery of Sb(V) into cells in which the parasite is internalized. Moreover, several macrophage mechanisms associated with parasite elimination depend on Ca +2 release from their own cellular stores.…”
Section: Resultsmentioning
confidence: 99%